Effects of Anisotropy and CO2 Wettability on CO2 Storage Capacity in Sandstone - Jun Young Song; Yeon Jong Jeong; Tae Sup Yun (Geofluids)
The geological sequestration of carbon dioxide (CO2) is an alternative strategy for mitigating global warming. The CO2 storage capacity is often characterized by the capillary pressure curve, which in turn depends on the pressure and temperature of the injected CO2 and the internal structure of the reservoir rocks. The key structural feature that influences the storage capacity in porous rocks is their inherent anisotropy. An experimental study was performed to investigate the optimal conditions for CO2 injection into an anisotropic sandstone. The capillary pressure curve and the residual CO2 saturation were determined by injecting three CO2 phases into the directionally cored sandstone specimens with different flow rates. The CO2 saturation in sandstone increased with increasing flow rate, resulting in asymptotic values. The storage capacity of CO2 was the highest in the order of liquid CO2 (LCO2), supercritical CO2 (scCO2), and gaseous CO2 (gCO2). It was also the highest when the direction of CO2 injection was normal in relation to the embedded sandstone layers. The in situ cored sandstone from the Janggi Basin in Korea was further tested to examine the effect of its pore size on the capillary pressure of CO2.